Descriptions of a new genus and three new species of Phasmatodea from Southwest China (Insecta: Phasmatodea) - Hennemann, Frank H.; Conle, Oskar V.; Zhang, Weiwei; Liu, Ye (Zootaxa, 2008)
The genus Parastheneboea Redtenbacher, 1908 is recorded for the first time from the Yunnan Province and Chongqing municipality, China. Two new species are described and illustrated: P. foliculata n. sp. from Yunnan based on the female and eggs, and P. simianshanensis n. sp. from Chongqing based on the male alone. The systematics of Parastheneboea Brunner v. Wattenwyl are briefly discussed with a list of species provided. Andropromachus Carl, 1913 is represented in China by only one species, A. guangxiense (Chen & He, 2000). The genus is briefly discussed and shown to be closely related to Neohirasea Rehn, 1904. An English translation of the original Chinese description of A. guangxiense (Chen & He) is provided. A re-description, a brief review, comments and a key to the species of Pericentrus Redtenbacher, 1908 are provided. The genus is shown to belong in the subfamily Lonchodinae Brunner v. Wattenwyl, 1893 and to be related to Menexenus Stål, 1875. Pericentrus appendiculatus Redtenbacher, 1908 is transferred to the genus Trychopeplus Shelford, 1919 (n. comb.) and the type-locality “Central-Java” shown to be wrong. Pericentrus Redtenbacher has so far not been recorded from China but is very likely to be present in South Xizang (= Tibet). The new genus Cnipsomorpha n. gen. is described for three highly mountainous species from Yunnan Province, Cnipsus apteris Liu & Cai, 1992, Cnipsus colorantis Chen & He, 1996 and Cnipsomorpha erinacea n. sp., of which the latter is designated as the type-species. All three species are only known from the females. The egg of C. erinacea n. sp. is the only one known from the genus and briefly described and illustrated. The new genus is related to Parapachymorpha Brunner v. Wattenwyl, 1893, and hence provisionally attributed to Phasmatidae: Pachymorphinae: Gratidiini. A key is provided to distinguish between the species of Cnipsomorpha n. gen.. English translations of the original Chinese descriptions of Cnipsus apteris Liu & Cai, 1992 and Cnipsus colorantis Chen & He, 1996 are presented. Type-specimens of new taxa are deposited in IZCAS, INCA and the collections of the authors.